2014
DOI: 10.1002/qua.24795
|View full text |Cite
|
Sign up to set email alerts
|

Neural network‐based approaches for building high dimensional and quantum dynamics‐friendly potential energy surfaces

Abstract: Development and applications of neural network (NN)-based approaches for representing potential energy surfaces (PES) of bound and reactive molecular systems are reviewed. Specifically, it is shown that when the density of ab initio points is low, NNs-based potentials with multibody or multimode structure are advantageous for representing high-dimensional PESs. Importantly, with an appropriate choice of the neuron activation function, PESs in the sum-of-products form are naturally obtained, thus addressing a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
153
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(155 citation statements)
references
References 126 publications
2
153
0
Order By: Relevance
“…The ML methods considered above are ignorant of symmetry. This can be addressed by explicit or implicit symmetrization [46,98,136,157]. ML typically requires relatively costly optimization of parameters (NN) or hyper-parameters (GPR, KRR) or extensive evolutionary searches (GA-inspired schemes).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ML methods considered above are ignorant of symmetry. This can be addressed by explicit or implicit symmetrization [46,98,136,157]. ML typically requires relatively costly optimization of parameters (NN) or hyper-parameters (GPR, KRR) or extensive evolutionary searches (GA-inspired schemes).…”
Section: Discussionmentioning
confidence: 99%
“…We only consider the use of ML for the solution of the vibrational and electronic SE or the KS equation or the Hohenberg-Kohn (HK) equation and not methods that aim to avoid such solutions (such as those directly mapping the molecular structure to the spectrum or energy or properties without solving for the density or wavefunction [29][30][31][32][33][34][35][36]); we also do not consider uses of ML for other types of quantum mechanical modelling or other types of differential or integral equations [37][38][39][40][41][42].We do not aim to present a comprehensive review but rather a survey allowing similarities and differences of ML uses in all these applications, as well as promising directions for future research, to transpire. This is not a review of ML methods; the key machine learning techniques that found use in quantum chemistry are well reviewed elsewhere [3-5, 43, 44], their description will not be repeated there; the reader is advised to consult the literature for their introduction, such as [45,46] for neural networks, [47,48] for Gaussian process regression (GPR), [49] for kernel ridge regression (KRR; note the similarity in the form of the function representation between GPR and KRR), [50] for genetic algorithms (GA) and [51] for particle swarm optimization. These methods as applied to quantum mechanics have recently been reviewed [44].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, a variety of different approaches to generating analytical forms for PESs have been developed and applied to a diversity of molecules and molecular complexes. Hence, PES¯tting has been and remains a vigorously studied problem; see, for example, a number of recent (since 2010) reviews [1][2][3][4][5][6][7][8][9] and the references cited therein. In this paper, the focus is on tting PESs based on high-level ab initio energies in sum-of-products form, and in particular using neural networks (NN) with exponential neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The two main categories for the representation of PESs can be divided into fitting methods and interpolation methods. Fitting methods include simple polynomial representations, many-body polynomials 3 and a broad variety of neural networks 4,5 . Interpolation methods proa) Electronic mail: mkowalew@uci.edu vide the possibility to represent the PES without the necessity of prior knowledge of its shape, and reproduce the function exactly at the sample points.…”
Section: Introductionmentioning
confidence: 99%